SILICON APPLICATION AND MYCORRHIZA INOCULATION PROMOTED LEUCAENA LEUCOCEPHALA GROWTH IN A SOIL HIGHLY CONTAMINATED BY MANGANESE (Nativa, 2022)
ABSTRACT: Arbuscular mycorrhizal fungi (AMF) can increase the acquisition of silicon (Si) and, therefore, alleviate the problems caused by metallic toxicity in plants, but this effect remains poorly understood. The objective was to evaluate the influence of Si application on the growth of Leucaena leucocephala inoculated with AMF (Claroideoglomus etunicatum) in a soil contaminated by manganese (Mn). We exposed plants to increasing levels of Si (0, 100, 200 and 400 mg kg-1) in the soil for 90 days. Intermediate levels of Si and AMF inoculation significantly increased shoot and root dry mass, the number of sheets, root system length and mycorrhizal colonization. The abundance of AMF spores decreased linearly with increasing levels of Si applied to the soil, suggesting a low correlation with mycorrhizal colonization. In addition to the higher Mn contents in the shoots and, mainly, in the roots, the combined application of Si and inoculation with AMF significantly reduced foliar toxicity by more than 40%, when compared to the absence of Si and AMF inoculation. Our results demonstrated a synergistic effect of AMF and Si in improving the growth and tolerance of L. leucocephala plants in soil contaminated by Mn.Keywords: heavy metals; stress; remediation; AMF; Mn toxicity. Aplicação de silício e inoculação de micorriza promove crescimento de Leucaena leucocephala em solo altamente contaminado por manganês RESUMO: Os fungos micorrízicos arbusculares (FMA) podem aumentar a aquisição de silício (Si) e, portanto, amenizar os problemas causados ​​pela toxidez metálica nas plantas, mas esse efeito ainda é pouco conhecido. O objetivo foi avaliar a influência da aplicação de Si no crescimento de Leucaena leucocephala inoculada com FMA (Claroideoglomus etunicatum) em solo contaminado por manganês (Mn). Expusemos as plantas a níveis crescentes de Si (0, 100, 200 e 400 mg kg-1) no solo por 90 dias. Níveis intermediários de Si e inoculação de FMA aumentaram significativamente a massa seca da parte aérea e radicular, o número de folhas, o comprimento do sistema radicular e a colonização micorrízica. A abundância de esporos de FMA diminuiu linearmente com o aumento dos níveis de Si aplicados ao solo, sugerindo uma baixa correlação com a colonização micorrízica. Além dos maiores teores de Mn na parte aérea e, principalmente, nas raízes, a aplicação combinada de Si e inoculação com FMA reduziu significativamente a toxidez foliar em mais de 40%, quando comparada à ausência de Si e inoculação de FMA. Nossos resultados demonstraram um efeito sinérgico de FMA e Si na melhoria do crescimento e tolerância de plantas de L. leucocephala em solo contaminado por Mn.Palavras-chave: metais pesados; estresse; remediação; FMA; toxidez por Mn.